Sea level rise, spatially uneven and temporally unsteady: Why the U.S. East Coast, the global tide gauge record, and the global altimeter data show different trends. Issue 20 (17th October 2013) - Ezer, Tal
Key Points The spatial pattern of sea level rise acceleration is explained Multidecadal climate variations unevenly affect sea level rise Discrepancies in global sea level rise from different observations are explained